PERMIT TO WORK SYSTEM (A Familiarization on Safe Working on Board of a Ship) - subiyanto subiyanto; Endah Fauziningrum (UNIMAR AMNI Semarang, 2020)
A job has the potential of causing serious injuries or death. It is necessary to formalize agreed upon work procedures. This prevents the instructions from being missed, forgotten or misinterpreted. It also works as a checklist to ensure that all the hazards, protective measures, work procedures and the general requirements are reviewed with and understood by the assigned worker(s). A work permit serves as a record of the authorization and the completion of the specific work. The authorization must be provided by the competent person after all the necessary conditions have been met. The purpose of this study is to familiarize permit to work system on board of a ship for a safe working environment. The data collecting method use is library research. All parties, the company, the officers and the assigned worker(s) have to commit and comply to all procedures and the requirements of the permit to work system. It has been provided by the regulator. It should be used as needed and required. KKeywords :System, Work permit, Safe working, Board, Ship